The Rapid Formation of the Metal-poor Milky Way - Turner Woody; Charlie Conroy; Phillip Cargile; Ana Bonaca; Vedant Chandra; Jiwon Jesse Han; Benjamin D. Johnson; Rohan P. Naidu; Yuan-Sen Ting (The Astrophysical Journal)
Our understanding of the assembly timeline of the Milky Way has been transforming along with the dramatic increase in astrometric and spectroscopic data available over the past several years. Many substructures in chemo-dynamical space have been discovered and identified as the remnants of various galactic mergers. To investigate the timeline of these mergers, we select main-sequence turnoff and subgiant stars (MSTOs) from the H3 survey, finding members in seven metal-poor components of the halo: Gaia-Sausage/Enceladus (GSE), the Helmi Streams, Thamnos, Sequoia, Wukong/LMS-1, Arjuna, and I’itoi. We also select out a metal-poor in situ population to facilitate comparison to the evolution of the Milky Way itself at these early epochs. We fit individual isochrone ages to the MSTOs in each of these substructures and use the resulting age distributions to infer simple star formation histories (SFHs). For GSE, we resolve an extended SFH that truncates ≈10 Gyr ago, as well as a clear age–metallicity relation. From this age distribution and measured SFH we infer that GSE merged with the Milky Way at a time 9.5–10.2 Gyr ago, in agreement with previous estimates. We infer that the other mergers occurred at various times ranging from 9 to 13 Gyr ago, and that the metal-poor in situ Galaxy built up within only a few billion years. These results reinforce the emerging picture that both the disk and halo of the Milky Way experienced a rapid assembly.